Impact of Digital Transformation on Strategic Change Processes in China - Huang, Chen (International Journal of Strategic Management, 2023)
Purpose: The aim of the study was to investigate the impact of digital transformation on strategic change processes in china. Methodology: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library Findings: The impact of digital transformation on strategic change processes in China has yielded several key findings. First, digital technologies have significantly accelerated the pace of strategic change, enabling companies to adapt swiftly to market dynamics. Second, digital tools have facilitated data-driven decision-making, enhancing the precision and effectiveness of strategic planning. Finally, successful strategic change in China increasingly hinges on digital capabilities, emphasizing the necessity for organizations to prioritize digital transformation as a core component of their strategic agenda. Unique Contribution to Theory, Practice and Policy: Resource-Based View (RBV) Theory, Institutional Theory & Innovation Diffusion Theory may be used to anchor future studies on impact of digital transformation on strategic change processes in china. Companies in China should invest in developing digital talent internally Policymakers in China should continually adapt regulations to accommodate the dynamic nature of digital transformation.